2012
DOI: 10.1177/0954407012464314
|View full text |Cite
|
Sign up to set email alerts
|

A decision-tree-based approach to smoke spike detection in a heavy-duty diesel engine

Abstract: Smoke spikes occurring during transient engine operation have detrimental health effects and increase fuel consumption by requiring more frequent regeneration of the diesel particulate filter. This paper proposes a decision tree approach to real-time detection of smoke spikes for control and on-board diagnostics purposes. A contemporary, electronically controlled heavy-duty diesel engine was used to investigate the deficiencies of smoke control based on the fuel-to-oxygenratio limit. With the aid of transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…While trying to determine the root cause of smoke spikes in electronically controlled diesel engines, previous work by the author and co-workers have found that the flow-nozzle based EGR flow estimate as well as the Volumetric Efficiency estimate can be significantly inaccurate during the turbocharger lag period (Brahma, 2011(Brahma, , 2013(Brahma, , 2014. The inaccurate estimation of in-cylinder Oxygen mass was responsible for the smoke/particulate matter spikes.…”
Section: Background Motivation and Existing Literaturementioning
confidence: 99%
“…While trying to determine the root cause of smoke spikes in electronically controlled diesel engines, previous work by the author and co-workers have found that the flow-nozzle based EGR flow estimate as well as the Volumetric Efficiency estimate can be significantly inaccurate during the turbocharger lag period (Brahma, 2011(Brahma, , 2013(Brahma, , 2014. The inaccurate estimation of in-cylinder Oxygen mass was responsible for the smoke/particulate matter spikes.…”
Section: Background Motivation and Existing Literaturementioning
confidence: 99%
“…The nonspike segments were not simulated in GTPower and simply predicted by simple global regression trained on transient snap-throttle data as per recommendations made in previous work. 3 The point-bypoint R 2 agreement was only 0.1347 but such a comparison is not indicative of predictive accuracy in this particular case because the opacity was measured a few meters downstream of the engine and was not instantaneously equal to the opacity at the exhaust manifold during transients. This is not only because of transport delay (the measured signal was aligned to ECM events by shifting the raw signal by 0.7 s, determined statistically, to account for sensor and transport delay) but also due to volume capacitance.…”
Section: Resultsmentioning
confidence: 96%
“…This new approach, termed the “nonparametric reduced dimensionality” (NPRD) modeling approach, was developed to address the lack of robustness and generality particularly inherent in empirical smoke or particulate matter (PM) emission models commonly used for transient calibration and control modeling. 13 The dual motivations for this work are as follows: (1) The ubiquitous presence of smoke from heavy duty engines in everyday life and (2) the lack of generality exhibited by empirical transient opacity or PM models trained on ECM estimated engine flows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations